Studies on 4 f-metal(III) complexes of N-thiophene-2-carboxamidosalicylaldimine - Singh B.; Singh P.K.; Tiwari V.P. (My University, 2025)
N-(thiophene-2-carboxamido) salicylaldimine (H2TCS) reacts with lanthanide chlorides in the presence of KOH to give complexes of the type K(Ln(TCS)2] [Ln=La(III), pr(III), Nd(III), Sm(III), Eu(III), Gd(III) and Dy(III)]. A tentative structure for these complexes has been suggested on the basis of molar conductance, TGA and DTA, magnetic susceptibility, electronic, infrared and1H and13C NMR data. The nephelauxetic ratio ( {Mathematical expression}), covalency (σ) and bonding parameter (b1/2) have been calculated from the electronic spectrum of the Nd(III) complex. A coordination number of six around the metal ion has been suggested. © 1991 Indian Academy of Sciences.